Synthesis and Melanogenesis Effect of 7,8-Dimethoxy-4-Methylcoumarin via MAPK Signaling-Mediated Microphthalmia-Associated Transcription Factor Upregulation - Kang, Min-Sung; Jang, Sung-Chan; Park, Taejin; Kim, MinSeon; Park, Jin-Soo; Chi, Won-Jae; Kim, Seung-Young (SAGE PUBLICATIONS INC, 2022)
Tyrosinase ultimately controls the melanogenesis rate of the skin, and tanning and haircare products generally induce the activation of tyrosinase. Moreover, various enzymes, including tyrosinase, tyrosinase-related protein 1 (TRP1), and tyrosinase-related protein 2 (TRP2), mediate melanogenesis in which microphthalmia-associated transcription factor (MITF) is a master regulator. One coumarin family member 7,8-dihydroxy-4-methylcoumarin (DHMC) shows extensive biological activities with beneficial health effects; however, it also induces cytotoxicity and its melanogenic effect has not been reported yet. Therefore, we first synthesized DHMC derivatives via methylation to obtain 7,8-dimethoxy-4-methylcoumairn (DMMC), and investigated the pro- or anti-melanogenic effects of DHMC and DMMC in B16-F10 melanoma cells as well as the underlying mechanism. DHMC showed cytotoxicity at all tested concentrations, whereas DMMC did not reduce cell viability, even at the high concentration. DMMC also drives the significant increase in intracellular melanin and tyrosinase activity. Moreover, DMMC induced MITF expression by significantly increasing tyrosinase activity, which activates the gene expression of TRP1 and TRP2. Western blotting confirmed that DMMC induced the activation of mitogen-activated protein kinase (MAPK) signaling by the phosphorylation of C-Jun N-terminal kinase (JNK), resulting in the increased melanin production and the decreased phosphorylation of protein kinase B. Collectively, this study showed the pro-melanogenic effect of DMMC and its potential as a safe tanning and dyeing agent.